The Sage handbook of developmental psychology and early childhood education - Whitebread, David; Grau, Valeska; Kumpulainen, Kritiina; McClelland, Megan M.; Perry, Nancy E.; Pino-Pasternak, Deborah (Los Angeles Sage Publications, 2019)
With the expertise of a body of international contributors from Australia, Canada, USA, UK, Finland, The Netherlands, Italy, Greece and Chile, this handbook explores key in-depth issues in quality Early Childhood Development and Education. Unlike previous publications in the discipline, this title combines research and practice to investigate emotional and social development, wellbeing and mental health, language, cultural environments, as well as the role of parents in a child's development.
Includes bibliographical references and index.
Keywords: Child development -- Handbooks, manuals, etc; Child psychology -- Handbooks, manuals, etc; Early childhood education -- Handbooks, manuals, etc